Rekonstruksi Nilai-nilai Pancasila dalam Undang-Undang - Madaskolay Viktoris Dahoklory; Lita Tyesta Addy Listya Wardhani (SASI, 2020)
Pancasila is the source of all sources of State law, by placing Pancasila as a source of state law, Pancasila has a function as a guiding star in the formation of national legal products. The purpose of the Writing is to analyze and understand the transformation of the values of Pancasila in the context of the renewal of national legal products and the mechanism of testing and harmonization of laws with the values of Pancasila. The research method used is juridical-normative and qualitative analysis. The results of the study show that several national legal products do not reflect Pancasila values, such as the water resources law, this was proven when the Constitutional Court issued its decision, which in essence the Constitutional Court stated that the law contrary to the values of Pancasila as implemented in the constitution. Therefore, the Government needs to increase its role in managing and harmonizing regulations as an effort to renew national legal products that are responsive in character.